EXPLORING THE LEGAL DIMENSION OF HEALTH COMMUNICATION: A POLICY ANALYSIS OF PATIENT DATA PRIVACY AND MEDICAL RIGHTS PROTECTION IN THE AGE OF DIGITALISATION - Andreas Harry; Gunawan Widjaja (ADISAM PUBLISHER, 2025)
Digitalisation in the healthcare sector is bringing about a major transformation in the way healthcare communication is conducted, especially regarding the management of patient data and the protection of medical rights. This study uses the literature method. The research findings found that current legal regulations are still not fully responsive to the rapid development of technology, so a more comprehensive policy update is needed. Emphasis is placed on the need for harmonisation between health technology innovation and ethical and legal principles to maintain the security of medical information. This article offers solutions to improve legal protection in health communication, with the aim of creating a digital health system that is safe, reliable, and effective for the community